Efeito da educação em neurociência da dor associado ao pilates na catastrofização para idosos com dor lombar crônica: ensaio randomizado controlado - Rossetti, Estefani Serafim (2020)
Pain Neuroscience Education (PNE) aims to reconceptualize maladaptive behaviors and modify erroneous pain beliefs. Objective: Analyze the effects of pain neuroscience education on pain catastrophization in elderly people with chronic low back pain who underwent pilates. Design and Method: This is a randomized controlled clinical trial. The participants were divided into two groups: Pilates Group associated with Education in Neurosciences of Pain - PEG and Pilates Group - PG. Inclusion criteria: age equal to or above 60 years old, main complaint of chronic non-specific low back pain, score indicating absence of cognitive alteration in the Mini Mental State Examination according to education and absence of depressive symptoms in the Geriatric Depression Scale. Exclusion criteria: having undergone non-pharmacological treatments for pain management in the last six months, being involved in regular sports activities, having fractures of the lower limbs, medical diagnosis of fibromyalgia, neoplasms and neurological impairment. The protocol for the PEG included three individual sessions of 30 minutes of PNE and 8 weeks of Pilates (twice a week, for 50 minutes each meeting. The PG obtained the same protocol as the Pilates. The primary outcome analyzed was pain catastrophization and secondary outcomes, kinesiophobia, disability and pain intensity. For comparisons of variables, the post-test using orthogonal contrasts was used. The sample calculation was carried out based on a pilot study and indicated 40 individuals per group. covariance analysis (ANCOVA) was performed between groups in relation to the deltas. Results: In intra-group comparisons, statistical differences were observed in the pre-post, pre-follow-up, post-follow-up moments with improvement of all variables studied in both groups.In the intergroup comparison, no association was found between the PEG and PG groups in the pre-post and follow-up moments in any of the variables studied through the ANCOVA covariance analysis. There is no evidence that the PEG obtained a greater change in results when compared to the PG. Discussion: The analyzes of intergroup comparisons of the pre and post differences in the variables catastrophization, kinesiophobia, disability and pain intensity did not show evidence that PEG had additional effects when compared to PG. A probable advantage of PNE was that dropout rates for PEG were lower than for PG, showing that PNE increased adherence to exercise. Conclusion: The results of this study indicate that the addition of PNE to the Pilates intervention did not lead to an additional effect for elderly people with nonspecific chronic low back pain. The clinical relevance of the study is that Pilates is a safe intervention for elderly people with non-specific chronic low back pain and PNE can increase adherence to exercise for this population. This study is registered on the platform of the Brazilian Registry of Clinical Trials Rebec, under the protocol U1111-1190-673.